4. ECONOMIC ASYMMETRY IN DRONE WARFARE A CASE STUDY OF IRAN'S SHAHED-136 OPERATION AGAINST ISRAEL'S IRON DOME DEFENSE SYSTEM - Ahmad Ilham Kamal; Muchammad Furqon Muchaddats; Ferdy Anggrian; Andromeda Yoga Pratama; Riza Suseno; Kurniawan; Dikasitama (Staf Komunikasi dan Elektronika, TNI Angkatan Udara, 2026)
The advent of low-cost loitering munitions has revolutionized modern warfare,creating a profound economic imbalance between offensive and defensive capabilities. In theMiddle East, the deployment of Iran's Shahed-136 drone against Israel's Iron Dome defensesystem serves as a prime example of a